Low seroprevalence and zero incidence rate of hepatitis E in men who have sex with men during a hepatitis A outbreak. Issue 8 (2nd December 2019) - Rodríguez‐Tajes, Sergio; Perpiñán, Elena; Leonel, Thais; Lens, Sabela; Mariño, Zoe; Pérez‐del‐Pulgar, Sofía; García‐López, Mireia; Pocurull, Anna; Koutsoudakis, George; Forns, Xavier
Abstract: Hepatitis E virus (HEV) and hepatitis A virus (HAV) are both secreted in feces. Despite HEV transmission in Europe is mainly zoonotic, person‐to‐person transmission has not been completely excluded. Men who have sex with men (MSM) constitute a high‐risk group for HAV mostly due to oral sex. We investigated the potential transmission of HEV during an acute hepatitis A (AHA) outbreak mainly affecting MSM. One hundred and two patients were diagnosed with AHA. Sixty‐nine (68%) self‐reported to be MSM, 75% of whom had high‐risk sexual behaviors and 46% had suffered previous sexually transmitted diseases. We collected serum from 85 (83%) patients during AHA. HEV‐IgG seroprevalence was not different among MSM (7%) compared with non‐MSM (8%) patients. Two patients had positive anti‐HEV‐IgM, but all samples tested negative for HEV‐RNA. These results suggest that HEV does not spread by sexual contact or person‐to‐person in our area.